Actions do speak louder than words: deterring plagiarism with the use of plagiarism-detection software. - Braumoeller, Bear F.; Gaines, Brian J. (PS: Political Science & Politics, 2001)
A study was conducted to examine the effects of explicitly warning political science students not to plagiarize and of using plagiarism-detection software on rates of plagiarism. Findings revealed that warning students was insufficient, but that revealing that the detection system would be used was a strong deterrent. One in eight papers was found to be problematic either because of casual plagiarism or blatant plagiarism. It was concluded that although the software is not perfect, its success rate was good enough to warrant its use.